CSR in an Asymmetric Duopoly with Environmental Externality. (24th February 2016) - Lambertini, Luca; Palestini, Arsen; Tampieri, Alessandro
Abstract : We investigate a linear state differential game describing an asymmetric Cournot duopoly with capacity accumulation á la Ramsey and a negative environmental externality (pollution), in which one of the firms has adopted corporate social responsibility (CSR) in its statute, and therefore includes consumer surplus and the environmental effects of production in its objective function. If the market is sufficiently large, the CSR firm sells more, accumulates more capital, and earns higher profits than its profit‐seeking rival.